2020
DOI: 10.1021/acs.chemmater.9b04309
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxo Clusters Improve the Optoelectronic Properties on Indium Phosphide Quantum Dots

Abstract: This study explored the effect of zinc precursors on the optical properties of InP quantum dots (QDs) by controlling the reactivity of zinc carboxylates via a simple thermal treatment. The formation of zinc oxo clusters, Zn4O­(oleate)6 and Zn7O2(oleate)10, during the thermal decomposition of zinc oleate was confirmed by matrix-assisted laser desorption/ionization-time-of-flight (MALDI-TOF) mass spectrometry. Using zinc oxo clusters as reaction precursors, high-quality InP QDs with a high photoluminescence quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…S3†). Thus, the observed trends were similar to those reported in our previous paper, 26 where we revealed that Zn oxo cluster can be used to generate Zn–phosphine complexes and regulate the kinetics of In(Zn)P core synthesis for obtaining In(Zn)P QDs with enhanced size uniformity. The conditions used to prepare the Zn oxo cluster also affected the quality of In(Zn)P QDs (Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…S3†). Thus, the observed trends were similar to those reported in our previous paper, 26 where we revealed that Zn oxo cluster can be used to generate Zn–phosphine complexes and regulate the kinetics of In(Zn)P core synthesis for obtaining In(Zn)P QDs with enhanced size uniformity. The conditions used to prepare the Zn oxo cluster also affected the quality of In(Zn)P QDs (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The Zn precursors were introduced during the nucleation process of In(Zn)P seeds due to their reaction kinetics regulator property which influenced on the quality of QDs. 26 In(Zn)P seeds were synthesized by the hot injection of the TMS 3 P solution, and the (Zn)In–P complex was then slowly introduced by a syringe pump. Each reaction batch was sampled after every 1 mL of the injected (Zn)In–P complex, and the specimens were subjected to UV-Vis and PLQY measurements without further purification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 The multiple QD-LED devices were interconnected by the transparent ICL. This device exhibited Pu et al 26 CdSe Electrochemically stable ligands T95@1,000 cd/m 2 > 3,800 hours for red T50@100 cd/m 2 > 10,000 hours for blue Won et al 31 InP-red HF-based surface etching for effective shell coating PLQY 98%, EQE 21.4%, T50@100 cd/m 2 > 1,000,000 hours Kim et al 32 InP 49 Typical structure Al-doped ZnO NP for ETL -Dai et al 51 Typical structure PMMA hole blocking layer EQE 20.5%, turn-on voltage 1.7 V, T50@100cd/m2 100,000 hours Sun et al 28 Inverted structure IML between ZnO/QD layers EQE 13.57% Lee et al 51 Inverted structure EDTA between ZnO/QD layers Luminance 187,186 cd/m2, EQE 5.5% Zhang et al 52 Tandem structure Stacking multiple QD-LED devices Current efficiency 41.5 cd/A, EQE 23.1% for red Current efficiency 121.5 cd/A, EQE 27.6% for green Current efficiency 17.9 cd/A, EQE 21.4% for blue Fabrication Process Coe-Sullivan et al 58 Spin-coating Phase separation during spincoating process…”
Section: Device Architecture Of Qd-ledmentioning
confidence: 94%
“…Kim et al introduced the Zn-oxo complex for maximising PLQY of the green InP QDs. 32 The Znoxo cluster was used to slow down the chemical reaction during QD synthesis as shown in Fig. 3 (b), resulting in dramatically achieving 95% PLQY of green InP QD.…”
Section: Nanoscale Horizons Accepted Manuscriptmentioning
confidence: 99%